Mediating Role of Employee Readiness to Change in the Relationship of Change Leadership with Employees' Affective Commitment to Change - Prema Sanjaya; Ni Made Dwi Ratnadai; Maria Mediatrix Ratna Sari; I Gusti Ayu Made Asri Dwija Putri (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine the effect of tax planning, leverage, bonus compensation, independent commissioners and public ownership on earnings management with profitability as a moderating variable. The independent variables in this study are tax planning, economic motivation, exam fees, bonus compensation, independent board of commissioners, public ownership, the dependent variable is earnings management and the moderating variable is profitability. This study uses moderating regression analysis (MRA) to determine the effect of tax planning, economic motivation, exam fees, bonus compensation, independent commissioners, public ownership, on earnings management with profitability as a moderating variable. In this study the determination of the sample using purposive sampling method with the number of samples used in this study as many as 39 companies with 117 samples observed. This study uses secondary data, data collected using documentation techniques. Testing the research hypothesis using SPSS 22.0 for Windows. The results showed that tax planning has a positive effect on earnings management. Leverage positive effect on earnings management. Bonus compensation does not have a positive effect on earnings management. Independent commissioners have a negative effect on earnings management. Public ownership has a negative effect on earnings management. Profitability strengthens influence tax planning on earnings management. Profitability cannot strengthen the effect of leverageto earnings management. Profitability can not strengthen the effect of bonus compensation to earnings management. Profitability strengthens influence independent board of commissioners on earnings management. Profitability strengthens influencepublic ownership of earnings management.